Solid Waste Management Practice and Its Associated Factors among Households in Gessa Town, Dawuro Zone, Southwest Ethiopia - Matiwos Maldaye; Desta Haftu; Sewunet Sako; Zenebe Jebero; Fikre Moga; Ayichew Alemu (Advances in Public Health)
Introduction. Human activities create waste, and the improper ways that waste is handled, stored, collected, and disposed of can pose risks to public health. The highest proportion of households practice their solid waste improperly in many developing countries, and the household’s status of solid waste management practices and its association with sociodemographic, knowledge, and institutional-related factors have never been clearly understood in Ethiopia, particularly in the study area. Therefore, this study aimed to assess the status of solid waste management practice and its associated factors among households in Gessa town, Dawro Zone, Southwest Ethiopia. Methods. A community-based cross-sectional study was conducted among 686 study participants from April 30 to June 15, 2021. Study participants were selected by using a computer-generated simple random sampling technique. The interviewer administered a semistructured questionnaire that comprised sociodemographic, household-related, and institutional-related factors were used for data collection. All collected data were entered into epi data version 4.6 and then exported to STATA version 14.0 for further analysis. Each independent variable with a p value <0.25 in the bivariable logistic regression was included in the multivariable logistic regression model. In multivariable logistic regression, variables having a p value <0.05 were considered statistically significant. Result. In this study, improper solid waste management practice was 86.2%. Unpracticed solid waste reduction at source (AOR = 5, 95% CI 2.9–8.9), householders’ poor knowledge about solid waste management (AOR = 5.2, 95% CI 2.6–10.3), and distance to the municipality disposal site greater than 30 minutes to one hour from householders' (AOR = 2.6, 95% CI 1.3–5.0) were found to be statistically significant associated factors for improper solid waste management practices of the households. Conclusions and Recommendations. The magnitude of improper solid waste management practices was high. Unpracticed solid waste reduction at source, householders’ poor knowledge about solid waste management, and distance from home to the waste disposal site were significantly associated factors. Therefore, policymakers, local government, and Gessa town health work units have to teach the community about solid waste management and solid waste generation minimization at the source and prepare standardized near-distance waste disposal sites to tackle contributing factors of improper solid waste management practice.